Demographic Dividend, Digital Transformation and Environmental Sustainability Nexus in South Asia - Sheikh, Muhammad Ramzan; Sahar, Mamoona; Ahmad, Rashid; Farooq, Fatima (Pakistan Journal of Humanities and Social Sciences, 2023)
The study explains the impact of digital transformation and environmental sustainability on the demographic dividend. Over the last few decades, remarkable demographic changes are founded in South Asian countries that provide a “window of opportunity” and cause sustainable development by promoting the working-age population. We have used Panel Autoregressive Distributed Lag Model (ARDL) to investigate the dynamic linkages between variables and estimate long-run and short-run results by applying different techniques. Data of all concerned variables are taken from 1972 to 2020 across all South Asian countries. The study employs two models to determine the relationship among variables. In the first model, long-run results show that mobile cellular subscriptions, internet users, urbanization growth, and trade are positively related to population ages (15-64) except for greenhouse gas emissions, governance index, and human capital index. In the second model, mobile cellular subscriptions, internet users, greenhouse gas emissions, urbanization growth, human capital index, and trade are positively related to secondary school enrollment except for the governance index. This study suggests that South Asian countries focus not only on the use of ICT but also promote other digitalization indicators for digital technology developments through investment. Further, policymakers may introduce policies to revamp the education system and create new opportunities to fulfill the labor market demand.